Revision of Marphysa de Quatrefages, 1865 and some species of Nicidion Kinberg, 1865 with the erection of a new genus (Polychaeta: Eunicidae) from the Grand Caribbean - Molina-Acevedo, Isabel C.; Carrera-Parra, Luis F. (Zootaxa, 2017)
Nine species of Marphysa from the Grand Caribbean Region are recognized and described based on the type and non-type specimens. One species is formally described as new: M. emiliae n. sp., and one is re-established as a valid species: M. fragilis Treadwell, 1911. The diagnosis of Nicidion Kinberg, 1865 is restricted based on novel features of the maxillary apparatus. Nicidion angeli (Carrera-Parra & Salazar-Vallejo, 1998) is redescribed, and two species that previously belonged to Marphysa, are transferred to Nicidion: N. longula (Ehlers, 1887) n. comb. and N. obtusa (Verrill, 1900) n. comb.. A new genus Treadwellphysa n. gen. is proposed to include those species having a newly described type of chaetae named spinifalcigers (exhibiting a mixture of falciger and spiniger blades), the base of maxillae II with a small elevation, and the ventral cirri with swollen base as transverse welt with short digitiform tip. Treadwellphysa n. gen. includes a new species, T. yucatanensis n. sp. and three other species previously included in Marphysa: T. amadae (Fauchald, 1977) n. comb., T. languida (Treadwell, 1921) n. comb., and T. veracruzensis (de León-González & Díaz-Castañeda, 2006) n. comb. Some morphological features are evaluated to clarify their variability with respect to specimen size. A key to Eunicidae genera, and keys to species of Marphysa and Treadwellphysa n. gen. from the Grand Caribbean region are given.